Characterisation of the probiotic qualities exhibited by lactobacilli strains isolated from the anogenital tract - Choo, Sulin; Chew, Boon How; Mohd Jamil, Amilia Afzan; Chew, Shu Yih; Meleh, Hadiza Umar; Than, Leslie Thian Lung (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Lactobacilli are well-documented probiotics that exert health benefits on their host. They exhibit characteristics that make them potential alternative treatments to address the antimicrobial resistance conundrum and diseases. Their mechanism of action varies with strain and species. Five lactobacilli strains previously isolated from the anogenital region were subjected to several assessments highlighted in the FAO/WHO document, ‘Guidelines for the Evaluation of Probiotics in Food’ to determine its suitability as potential probiotics. Methods: The five lactobacilli strains were subcultured onto Man de Rogosa agar (MRS). Their ability to auto- and co-aggregate was determined spectrophotometrically. Simultaneously, the cell surface hydrophobic properties of these strains towards xylene and toluene were evaluated using the microbial adhesion to hydrocarbon (MATH) test. The lactobacilli strains were also tested for their ability to withstand acid, bile and spermicide to determine their level of tolerance. Results: Lact. reuteri 29A, L. delbrueckii 45E and L. reuteri 29B exhibited the highest degree of auto- and co-aggregation properties. These lactobacilli strains also demonstrated high cell surface hydrophobicity, with the exception of L. delbrueckii 45E. Further tests to evaluate the isolated lactobacilli tolerance identified L. reuteri 29B as the most tolerant strain towards low pH (pH 2.5 for 4 h), high bile concentration (0.5% for 4 h) and high spermicides concentration (up to 10%). Conclusion: Out of the five lactobacilli strains which possessed high antimicrobial activities, L. reuteri 29B portrayed the best probiotic qualities with good auto- and co-aggregation abilities and high tolerance against acid, bile and spermicide.